Citizens Against Corruption: Report from the Front Line - and Landell-Mills, Pierre (Matador, 2013)
Citizens Against Corruption: Report From The Front Line tells the story of how groups of courageous and dedicated citizens across the globe are taking direct action to root out corruption. It shows how people are no longer prepared to accept the predatory activities of dishonest officials and are challenging their scams. It draws on over 200 unique case studies that describe initiatives undertaken by 130 civil society organisations (CSOs) which engage directly with public agencies to stop the bribery and extortion that damages peoples' lives and obstructs social and economic progress. This book challenges the notion that, at best, civil society can only have a marginal impact on reducing corruption and argues that aid donors need to radically rethink their assistance for governance reform. Part 1 analyses the role citizens can play in fighting corruption and promoting good governance and briefly tells the story of the Partnership for Transparency Fund (PTF). Part 2 presents studies of India, Mongolia, Philippines, and Uganda - each with its unique history and distinctive circumstances - to illustrate activities undertaken by CSOs to root out corruption, including the tools and approaches that are being used to build pressure on corrupt public agencies to become transparent and accountable. Part 3 addresses key themes - strengthening the rule of law, putting in place effective national anti-corruption strategies and institutions, making public buying and selling honest, promoting grassroots monitoring of public expenditures and the provision of public services, mounting media campaigns to expose and defeat corruption, and empowering ordinary citizens to keep watch on what actually happens at the point of delivery of public services. Part 4 is a summary of lessons learnt and explores the potential, as well as the risks and limitations, of civic activism in a world where greed and dishonesty is the norm. Finally, the book explores the opportunities and dangers faced by aid donors in supporting local CSOs and charts a way forward. Citizens Against Corruption: Report From The Front Line will be of interest to staff working in CSOs and aid agencies, policy analysts and researchers concerned about corruption and poor governance.